Evaluasi Program Bimbingan Remaja Usia Sekolah di Tengah Maraknya Permohonan Dispensasi Nikah di Provinsi Aceh - Ilyas Hasan, Afrizal (JURNAL ILMIAH GEMA PERENCANA, 2025)
This policy paper explains that adolescents are in a transition period and are vulnerable to violations due to bad company. Thus, many requests for marriage dispensation are made due to mistakes and violations committed by adolescents. The high number of marriage dispensations is inversely proportional to the existence of the School Age Adolescent Guidance (BRUS) program. The purpose of this study is to conduct a critical analysis of the evaluation of the BRUS program in achieving the tasks and development of adolescents and the phenomenon of the many requests for marriage dispensation in Aceh Province. This study was conducted using a qualitative approach. The data used are primary and secondary. Data were analyzed using the countenance stake and AHP models. The results of the study: 1) the implementation of the BRUS program still has many obstacles, namely lack of budget, limited quality and quantity of human resources, lack of facilities, lack of innovative materials, no consistency in budget allocation, evaluation errors; 2) evaluation with countenance stake produces information that weaknesses in the BRUS program began since the development of policies that did not analyze resources, so the program was implemented with various resource limitations, both tangible and intangible resources; 3) Evaluation using stake countenance resulted in 6 (six) policy issues that were selected for their urgency weight using AHP and obtained the development of resources as human capital that needs to be transformed. Human capital is developed with strategic positioning, human resource accountability, human resource technology, and human resource competence.